2011
DOI: 10.1371/journal.pone.0025126
|View full text |Cite
|
Sign up to set email alerts
|

Colonization-Competition Tradeoffs as a Mechanism Driving Successional Dynamics in Ectomycorrhizal Fungal Communities

Abstract: Colonization-competition tradeoffs have been shown to be important determinants of succession in plant and animal communities, but their role in ectomycorrhizal (ECM) fungal communities is not well understood. To experimentally examine whether strong spore-based competitors remain dominant on plant root tips as competition shifts to mycelial-based interactions, we investigated the mycelial competitive interactions among three naturally co-occurring ECM species (Rhizopogon occidentalis, R. salebrosus, and Suill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 35 publications
3
39
0
1
Order By: Relevance
“…We have also shown that S. subaureus can colonize two Pinaceae host species, suggesting that this species is a host generalist rather than a Quercus specialist. Because the capacity to colonize alternative hosts can be controlled either at the point of spore germination or during downstream signaling processes, host identity may influence colonization differently depending on whether spores must be germinated in order to establish fungal presence, or whether extant mycorrhizas are already present on neighboring plants (Molina et al ., ; Kennedy et al ., ). Consistent with earlier studies (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have also shown that S. subaureus can colonize two Pinaceae host species, suggesting that this species is a host generalist rather than a Quercus specialist. Because the capacity to colonize alternative hosts can be controlled either at the point of spore germination or during downstream signaling processes, host identity may influence colonization differently depending on whether spores must be germinated in order to establish fungal presence, or whether extant mycorrhizas are already present on neighboring plants (Molina et al ., ; Kennedy et al ., ). Consistent with earlier studies (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Spores from the nine S. subaureus sporocarps were collected following the methods outlined by Kennedy et al . () and stored in moistened sterile growth media at 4 ° C until use. Plant growth medium consisting of a 2 : 2 : 1 mix of peat (no.…”
Section: Methodsmentioning
confidence: 99%
“…Species that are less rapid colonizers, on the other hand, should be better resource competitors, which ultimately enables them to colonize, and eventually to dominate, habitats in which early colonizers are already abundant (Tilman 1994, Connell and Slatyer 1977). This tradeoff has been demonstrated in laboratory experiments with protozoans (Cadotte et al 2006) and fungi (Kennedy et al 2011), and in a field study with terrestrial plants (Gleeson and Tilman 1994). …”
Section: Introductionmentioning
confidence: 87%
“…There are three key abiotic factors that determine the presence of ectomycorrhizal fungi in the soil: temperature, pH, and nitrogen (Erland and Taylor 2002). There is also another factor to take into account: competitive interactions between fungi may significantly influence temporal patterns of the ectomycorrhizal community structure (Kennedy et al 2011b).…”
Section: Ectomycorrhizae Patch Dynamics In the Rootsmentioning
confidence: 99%